2006
DOI: 10.1371/journal.pmed.0030101
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide Protects against Ethanol-Induced Apoptotic Neurodegeneration in the Developing Mouse Brain

Abstract: BackgroundExposure to alcohol during brain development may cause a neurological syndrome called fetal alcohol syndrome (FAS). Ethanol induces apoptotic neuronal death at specific developmental stages, particularly during the brain-growth spurt, which occurs from the beginning of third trimester of gestation and continues for several years after birth in humans, whilst occuring in the first two postnatal weeks in mice. Administration of a single dose of ethanol in 7-d postnatal (P7) mice triggers activation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
100
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(102 citation statements)
references
References 60 publications
(69 reference statements)
2
100
0
Order By: Relevance
“…Reactive oxygen species can involve superoxide free radicals, hydrogen peroxide, singlet oxygen, nitric oxide (NO), and peroxynitrite (Chong et al, 2005e). Most species are produced at low levels during normal physiological conditions and are scavenged by endogenous antioxidant systems that include superoxide dismutase (SOD), glutathione peroxidase, catalase, and small molecule substances such as vitamins C and E. Other closely linked pathways to oxidative stress may be tempered by different vitamins, such as vitamin D 3 (Regulska et al, 2007) and the amide form of niacin or vitamin B 3 , nicotinamide (Chlopicki et al, 2007;Chong et al, 2002d;Feng et al, 2006;Hara et al, 2007;Ieraci and Herrera, 2006;Lin et al, 2000;.…”
Section: Epo and Cellular Oxidative Stressmentioning
confidence: 99%
“…Reactive oxygen species can involve superoxide free radicals, hydrogen peroxide, singlet oxygen, nitric oxide (NO), and peroxynitrite (Chong et al, 2005e). Most species are produced at low levels during normal physiological conditions and are scavenged by endogenous antioxidant systems that include superoxide dismutase (SOD), glutathione peroxidase, catalase, and small molecule substances such as vitamins C and E. Other closely linked pathways to oxidative stress may be tempered by different vitamins, such as vitamin D 3 (Regulska et al, 2007) and the amide form of niacin or vitamin B 3 , nicotinamide (Chlopicki et al, 2007;Chong et al, 2002d;Feng et al, 2006;Hara et al, 2007;Ieraci and Herrera, 2006;Lin et al, 2000;.…”
Section: Epo and Cellular Oxidative Stressmentioning
confidence: 99%
“…Investigations of basic mechanisms not only may lead to better AED selection on an individual basis, but also could lead to preventive therapies. For example, nicotinamide can protect against ethanol-induced apoptotic neurodegeneration in the developing mouse brain [92].…”
Section: Basic Mechanismsmentioning
confidence: 99%
“…These agents can involve superoxide free radicals, hydrogen peroxide, singlet oxygen, nitric oxide (NO), and peroxynitrite (Chong, et al, 2005e). Most species are produced at low levels during normal physiological conditions and are scavenged by endogenous antioxidant systems that include superoxide dismutase, glutathione peroxidase, catalase, and small molecule substances such as vitamins C and E. Other closely linked pathways to oxidative stress may be tempered by different vitamins, such as vitamin D 3 (Regulska, et al, 2007) and the amide form of niacin or vitamin B 3 , nicotinamide (Chlopicki, et al, 2007, Chong, et al, 2002d, Hara, et al, 2007, Ieraci and Herrera, 2006.Throughout the body, cell survival and lifespan is tied to the presence of oxidative stress and the subsequent induction of apoptotic cell injury , De Felice, et al, 2007, Lin and Maiese, 2001). It has recently been shown that genes involved in the apoptotic process are replicated early during processes that involve cell replication and transcription, suggesting a much broader role for these genes than originally anticipated (Cohen, et al, 2007).…”
mentioning
confidence: 99%
“…These agents can involve superoxide free radicals, hydrogen peroxide, singlet oxygen, nitric oxide (NO), and peroxynitrite (Chong, et al, 2005e). Most species are produced at low levels during normal physiological conditions and are scavenged by endogenous antioxidant systems that include superoxide dismutase, glutathione peroxidase, catalase, and small molecule substances such as vitamins C and E. Other closely linked pathways to oxidative stress may be tempered by different vitamins, such as vitamin D 3 (Regulska, et al, 2007) and the amide form of niacin or vitamin B 3 , nicotinamide (Chlopicki, et al, 2007, Chong, et al, 2002d, Hara, et al, 2007, Ieraci and Herrera, 2006.…”
mentioning
confidence: 99%